Business Process Outsourcing: A case study on a Finance & Accounting function in an IT industry - Hoo, Yuen Mei Sharon (2009)
Over the past few years, the proliferation of networking technology and growing affluence of emerging economies has led to further globalization of major corporations. As competition intensifies around the world, companies were constantly challenged to restructure their business by reducing cost and maximizing shareholder value. Outsourcing is gaining precedence as a viable solution for companies seeking to reduce its cost structure as well as focus on their core competency. This created exponential growth in outsourcing across the globe and particularly in low-cost countries such as India and China. While outsourcing is viewed as an essential strategic tool for managers, many companies embark on this venture without sufficiently preparing their organization on the anticipated changes. This paper attempts to understand what it takes for a company to implement a successful outsourcing initiative by taking an end-to-end view. It examines the rationale behind the outsourcing decision; provide insights on the challenges of implementation and the role of change management.